1998
DOI: 10.1063/1.368935
|View full text |Cite
|
Sign up to set email alerts
|

Paraconductivity in YBa2Cu3O7 and YBa2Cu3O7 thin film composites with cerium oxide and gold

Abstract: The paraconductivity for thin films of YBa2Cu3O7 (YBCO) and composites of YBCO with CeO2 and gold was investigated and analyzed using the Aslamazov and Larkin theory. Plain YBCO thin films sputter deposited on MgO, SrTiO3, and yttrium stabilized zirconium typically showed no dimensional crossover, were described by three dimensional (3D) fluctuation conductivity, and had a critical slope just above the critical region in agreement with the prediction of theory. With few exceptions, the CeO2 and gold composite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 26 publications
0
4
1
Order By: Relevance
“…The 3D-2D crossover temperature (T 3D−2D ) was determined from the intersection of the two linear parts in the mean field regions. Chauskas and Allen [37] have found that T 3D−2D increases with increasing secondary phases, which has not been observed in our studies.…”
Section: Resultscontrasting
confidence: 89%
“…The 3D-2D crossover temperature (T 3D−2D ) was determined from the intersection of the two linear parts in the mean field regions. Chauskas and Allen [37] have found that T 3D−2D increases with increasing secondary phases, which has not been observed in our studies.…”
Section: Resultscontrasting
confidence: 89%
“…Unambiguous determination of T c , however, is difficult in cuprate superconductors due to the presence of fluctuation effects, which round the critical behavior of any observable near T c [10,11]. We have used the derivative of the resistance data as a function of temperature ( dR dT ), with T c defined as the peak position of this derivative, as has been done by many others [10,12,13]. The zero resistance temperature, T c0 , is defined as the temperature at which the resistance measured with decreasing temperature goes below the resolution.…”
Section: Methodsmentioning
confidence: 99%
“…Both the methods however do not rule out error in T c determination since the exponent in the SCOPF region varies over a large range. We have used the derivative of the resistivity data as a function of temperature ( dρ dT ), with T c defined as the peak position of this derivative (figure 1) as has been done by many [8,9,14]. The effect of uncertainty in the determination of the T c results in a temperature range corresponding to the critical region, where the excess conductivity sensitively depends on the reduced temperature [15,16].…”
Section: Methods Of Data Analysismentioning
confidence: 99%
“…On the other hand, the critical region just above T c has a strong dependence on the microstructure of the YBCO samples [8,9], which in turn depends on the Ag content in the films. Lobb [20] has theoretically analysed the critical fluctuations and defined the critical region as…”
Section: Mesoscopic Inhomogeneitymentioning
confidence: 99%
See 1 more Smart Citation